دافعية المعلمين للإنجاز في ظل نمط الإشراف التربوي دراسة ميدانية بمدينة ورقلة (Revue El-Wahat pour les Recherches et les Etudes, 2023)
ملخص:      هدفت الدراسة الحالية إلى الكشف عن الفروق في دافعية انجاز المعلمين تبعا لنمط الإشراف التربوي السائد من وجهة نظر المعلمين، وهذا بعد تكييف مقياس (الأزرق، 2000) مع البيئة المحلية. وتطبيقه على عينة بلغ تعدادها (196) معلما ومعلمة. وبعد تحليل البيانات أظهرت النتائج أن:- مستوى دافعية المعلمين للانجاز مرتفعة.- النمط الإشرافي السائد هو النمط الديمقراطي يليه النمط الأوتوقراطي ثم النمط الترسلي.- وجود فروق دالة إحصائيا بين درجات أفراد عينة الدراسة على مقياس دافعية الانجاز تعزى لنمط الإشراف التربوي ولصالح النمط الديمقراطي. كما وجدت فروق في دافعية الانجاز بين نمطي الإشراف الترسلي والأوتوقراطي ولصالح هذا الأخير.كلمات دالة: دافعية إنجاز, إشراف تربوي.   Abstract:     The Study Aimed To Detect Differences In The Motivation For Teacher Achievement According To The Prevailing Pattern Of Educational Supervision From The Point Of View Of Teachers After Adapting The Scale (El-Azrak, 2000) To The Local Environment To A Sample Of 196 Teachers.After Analyzing The Data, The Results Showed That:- The Level Of Motivation Of Teachers For Achievement Is High.- The Prevailing Supervisory Pattern Is The Democratic Pattern, Followed By The Autocratic And The Laissez-Faire Pattern.- The Existence Of Statistically Significant Differences Between The Grades Of The Study Sample On The Measure Of The Motivation Of Achievement Due To The Pattern Of Educational Supervision And In Favor Of The Democratic Pattern. There Were Also Differences In The Motivation For Achievement Between The Patterns Of Laissez-Faire And Autocratic Supervision And In Favor Of The Latter. Key Words: Motivation For Achievement, Educational Supervision.